2008
DOI: 10.1128/mmbr.00041-07
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Persistence of the Molybdopyranopterin-Containing Sulfite Oxidase Protein Fold

Abstract: SUMMARY The importance of molybdoenzymes is exemplified both by the debilitating and fatal human diseases caused by their deficiency and by their persistence throughout evolution. Here, we show that the protein fold of the molybdopyranopterin-containing domain of sulfite oxidase (the SUOX fold) can be found in all three domains of life. Analyses of sequence data and protein structure comparisons (secondary structure matching) show that the SUOX fold is found in enzymes that have quite distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 93 publications
(161 reference statements)
1
34
0
Order By: Relevance
“…NR belongs to the sulfite oxidase fold (SUOX) class of proteins, and sub-arrangements of the domains that comprise NR are analogous to independent extant enzymes, such as sulfite oxidase, cytochrome b5 reductase, and ferredoxin reductase-type enzymes (Workun et al 2008;Karplus and Bruns 1994;Campbell 2001). The domain arrangement of the NR gene is linear with respect to protein function, suggesting that NR evolved by domain shuffling and terminal exon fusion (Workun et al 2008;Campbell 2001).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…NR belongs to the sulfite oxidase fold (SUOX) class of proteins, and sub-arrangements of the domains that comprise NR are analogous to independent extant enzymes, such as sulfite oxidase, cytochrome b5 reductase, and ferredoxin reductase-type enzymes (Workun et al 2008;Karplus and Bruns 1994;Campbell 2001). The domain arrangement of the NR gene is linear with respect to protein function, suggesting that NR evolved by domain shuffling and terminal exon fusion (Workun et al 2008;Campbell 2001).…”
Section: Discussionmentioning
confidence: 98%
“…The domain arrangement of the NR gene is linear with respect to protein function, suggesting that NR evolved by domain shuffling and terminal exon fusion (Workun et al 2008;Campbell 2001). Although terminal exon fusion is considered to be a major contributor to the formation of novel domain arrangements (Moore et al 2008), a significant number of multi-domain proteins have been identified where a novel domain has been inserted within a preexisting domain (Selvam and Sasidharan 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cj0379 is a member of a distinct group of molybdoenzymes (the YedY family) that contain a simple molybdopterin (MPT) cofactor and which are present in a large number of diverse prokaryotes (Workun et al, 2008). Most of the proteins homologous to Cj0379 are encoded in a two-gene operon, designated yedYZ in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes, known as mononuclear Mo/W enzymes, play pivotal roles in metabolism, global geochemical cycles, and microbial metabolic diversity (2)(3)(4)(5). Their active sites, comprising a Mo or W ion and one or two pyranopterins, catalyze a diversity of redox transformations spanning a reduction potential range of approximately one volt.…”
mentioning
confidence: 99%
“…This form is assigned to the xanthine dehydrogenases, and in its cytosine dinucleotide form to the bacterial carbon monoxide dehydrogenases and aldehyde dehydrogenases (these enzymes are referred to collectively as the XDH family). It is also assigned to the sulfite oxidases and plant nitrate reductases [SUOX family (1,5)]. …”
mentioning
confidence: 99%